Population dynamics and types of habitats at breeding sites of raptors (Falconiformes) of the Donetsk Ridge along a gradient of anthropogenic disturbance - M. O. Vysochyn (Regulatory Mechanisms in Biosystems, 2019)
Studies of diurnal birds of prey may be quite indicative of the state of natural ecosystems and of the level of impact of human-induced factors on their functions. The aim of this work was to analyse the long-term dynamics of the raptor populations within the Donetsk Ridge, to identify which habitat or habitat mosaics are preferred in nesting territories and home ranges depending on the level of anthropogenic transformation of the environment. The studies were conducted in 1999–2019. The total length of the walking routes was 2,864 km while a distance of 1,548 km was covered by car routes. 306 nests of the birds of prey or those potentially belonging to the members of this group were found and re-examined. The long-term dynamics of the population of Falconiformes was characterized by a general decline in the numbers of most species. There was a loss of representatives of the boreal and desert-steppe faunistic complexes and simultaneous increase in the participation of representatives of the nemoral and forest steppe faunistic complexes associated with the floodplain forests of the Siversky Donets River valley and the bayrak oak forests of the central part of the Donetsk Ridge. The impact of the anthropogenic factor on the dynamics of the population of the birds of prey is ambiguous. For the species which are sensitive to changes in the environment, such as the European Honey Buzzard, the Northern Goshawk, the Merlin and the Red-footed Falcon, a general negative dynamics of the populations is observed. The positive trend in the numbers of the Long-legged Buzzard and the Saker Falcon is linked to the expansion of the both species into the territory of the Donetsk Ridge. The habitat structure of the nesting territories is quite diverse in different species of diurnal birds of prey. This is especially noticeable in the ratio of forest and grassland habitats. Based on the selectivity index, we found that the vast majority of the raptors of the Donetsk Ridge prefer temperate broad-leaved forests when choosing nesting territories. The structure of the home ranges of all forest species of diurnal birds of prey not only depends on the optimal ratio of open and forested areas but on the presence of ecotones of considerable length which originated in the complex mosaics of habitat complexes. The stable number of dendrophiles and the disappearance (decrease in number) of sclerophiles and campophiles indicates the least anthropogenic transformation of forest habitats and a radical transformation of open spaces – meadows and steppes. The most successful were eurytopic birds of prey and species with pronounced anthropotolerance.